Prevalence of needlestick and sharps injuries in the healthcare workers of Iranian hospitals: an updated meta-analysis - Reza Ghanei Gheshlagh; Marzieh Aslani; Fidan Shabani; Sahar Dalvand; Naser Parizad (Komiyama Printing Co. Ltd, 2018)
Abstract Background Needlestick and sharps injuries (NSIs) are critical occupational risk among health care workers (HCWs), which is extremely worrying due to the potential risk of transmitting bloodborn pathogens (BBPs). This study was carried out to evaluate the prevalence of NSIs among Iranian HCWs. Methods In this systematic review and meta-analysis, the key terms percu* injur*, needle* stick injur*, needlestick* injur*, or sharp* injur* were searched in the Scientific Information Database (SID), MagIran, IranMedex, Google Scholar, Science Direct, PubMed, and Scopus. A prefabricated checklist, including variables: first author, publication year, study population, sample size, gender, total prevalence of needlestick in each gender, type of questionnaire, region, and type of hospitals, was used to extract data from the selected articles included which were published between 2003 and 2016. Results The analysis showed that the prevalence of NSIs in the Iranian HCWs was 42.5% (95% CI 37-48). Moreover, the prevalence of NSIs was more in women (47%; 95% CI 36-58) compared to men (42%; 95% CI 26-58). Conclusion Given the high prevalence of NSIs, it is necessary to supply safe needles and instruments, hold training programs focused on new methods of using sharp objects safely, observe safety principles and standards, reinforce the practical skills of personnel, and pay more attention to reporting and improving occupational behaviors like avoiding needle recapping in order to reduce the prevalence of NSIs and consequently reduce potential risk of transmission of BBPs.